An Analysis of Justice in Tapera Based on the Perspective of Jurgen Habermas' Critical Theory and John Rawls' Theory of Justice - Firdaus, Kusuma; Utama, Yos Johan; Putrijanti, Aju (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Government Regulation Number 21 of 2024 was designed and issued to help Indonesian people who need financial support to own their first home. However, a few days after the regulation was enacted, the People's Housing Savings (Tapera) policy drew criticism from the public. This program is considered to burden low-income workers and is not fair enough for people from the middle to upper income group. This research aims to apply both theories, namely Jurgen Habermas's Critical Theory and John Rawls' Theory of Justice in the context of the Tapera Program.This research is a normative legal research using a statute approach. Data collection was carried out through literature studies of various legal sources and journals about Tapera.  The results of the study show that based on the perspective of Jurgen Habermas's Critical Theory and John Rawls' Theory of Justice, he emphasizes the importance of transparency, active participation, and protection of individual rights in the implementation of Tapera's policies. Based on Habermas' perspective, an inclusive public space is needed to ensure the participation of all parties in discussions and decision-making related to Tapera, with the aim of achieving social justice through rational communication. Meanwhile, Rawls' theory of justice emphasizes equal access to basic opportunities and a fair distribution of benefits for Tapera participants, regardless of social or economic status. The evaluation of Tapera's policies needs to consider these aspects to ensure justice in accordance with the social and democratic principles advocated by these two theories.